فاعلية نموذج التعلم القائم على المشروعات (Project Based Learning) في تنمية مهارات فهم المقروء في المطالعةِ - Teuku Sanwil (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2026)
This study aims to examine the effectiveness of the Project-Based Learning (PBL) model in enhancing reading comprehension skills in Mutala'ah among second-semester students of the Arabic Language Education Program at STIT Al-Hilal Sigli during the 2025/2026 academic year. Reading comprehension is one of the fundamental language skills that plays a significant role in developing students' linguistic competence and critical thinking. However, the teaching of Mutala'ah continues to face several challenges, including the predominance of teacher-centered instructional approaches, limited student engagement in classroom activities, and insufficient opportunities for collaborative and inquiry-based learning, all of which negatively affect students' comprehension of Arabic texts. This study employed a quantitative approach using a one-group pretest–posttest quasi-experimental design. The participants consisted of five second-semester students selected through a total sampling technique. Data were collected through pretest and posttest instruments, as well as classroom observations, and were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test. The findings indicated a substantial improvement in students' reading comprehension skills following the implementation of the Project-Based Learning model. The mean score increased from 57.6 in the pretest to 82.4 in the posttest, demonstrating that Project-Based Learning effectively promotes classroom interaction, independent learning, and students' ability to analyze and comprehend Arabic texts more deeply. The study concludes that Project-Based Learning is an effective instructional model for teaching Mutala'ah in Arabic Language Education programs. It can be adopted as an alternative instructional approach in higher education to improve reading comprehension skills, enhance students' learning motivation, and foster active participation in the learning process.